Masculinities in mid-twentieth-century Irish fiction and culture, 1931-1965 the men we dreamed of - Wright, Loic; Wright, Loic (Routledge, Taylor & Francis Group, 2026)
"Masculinities in Mid-Twentieth-Century Irish Fiction and Culture, 1931-1965 is a critical analysis of the construction, consolidation, and regulation of post-colonial Irish masculinity as evidenced by Irish fiction published during the mid-twentieth century. Investigating the years of the Irish Free State, Éire, and the Republic of Ireland, this book uses the years preceding the enactment of Bunreacht na hEireann (the Irish Constitution) in 1937 and the years following the First Programme for Economic Expansion in 1958 as its span for research. The analysis in this book incorporates contextual work on the masculinities of election rhetoric, Church and State visions of an idealised Irish masculinity, and the role of popular culture and fiction in promoting or rejecting official versions of Irish manhood. Therein, this book crucially analyses both critically acclaimed Irish authors such as Kate O'Brien, John McGahern, and Elizabeth Bowen alongside lesser-known writers who fell victim to the mid-century's rigorous culture of censorship such as M. J. Farrell, Norah Hoult and John Broderick. Wright's research in this book provides a holistic approach to scrutinising the construction of postcolonial Irish masculinity, including analysis on drinking culture, civil service employment, queer relationships, and the value of violence in masculine currencies"-- Provided by publisher
Includes bibliographical references and index
Keywords: English fiction -- Irish authors -- 20th century -- History and criticism.; Masculinity in literature; Men in literature; Literature and society -- Ireland -- History -- 20th century; Literary criticism